Some aspects of the autecology of Rhizoclonuium riparium (Roth) Harv. with special reference to its growth in the maturation ponds of the Grahamstown sewage works - Snook, Deborah Jane (Rhodes University, Faculty of Science, Botany Department, 1986)
During 1982 benthic and floating filamentous algal mats appeared in the maturation ponds of the Grahamstown Sewage Disposal Works. These mats clogged the ponds and reduced the efficiency by which the effluent was purified. As they continued to be a problem despite numerous efforts to remove them, this study was initiated to investigate the alga, establish why it was successful in the pond environment, and how its growth could be controlled. The physico-chemical environment of a representative maturation pond was characterised while laboratory studies were conducted to investigate the growth, photosynthetic and respiratory characteristics in the alga. The alga was identified as Rhizoclonium riparium (Roth) Harv. although its morphological variability was greater than that reported in the literature. Growth and photosynthetic studies indicated that the alga favoured temperatures between 20 and 30â °C and relatively high light intensity (700Î¼E.mâ »Â².sâ »Â¹) and that it was highly productive. In addition, the alga exhibited photoadaptive ability, although it seemed to be sensitive to photoinhibition. Its success in the maturation pond was attributed to the favourable physico-chemical environment, particularly the high transparency of the effluent which allowed the penetration of PAR to the pond floor and to the alga's ability to adapt to the change in environment when it floated from the pond floor to its surface. Although the algal mats contribute to the oxidation of the effuent within the maturation pond, they are generally detrimental to the system because they shade the water column and inhibit wind-induced mixing. Recommendations on methods of controlling of the mats are presented.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Green algae; Marine algae -- South Africa -- Grahamstown; Estuarine ecology -- South Africa -- Grahamstown